Modelling the Role of Pragmatic Plasticity in the Evolution of Linguistic Communication - Hoefler, Stefan H (The University of Edinburgh, 2009)
For a long time, human language has been assumed to be genetically determined and therefore the product of biological evolution. It is only within the last decade that researchers have begun to investigate more closely the domaingeneral cognitive mechanisms of cultural evolution as an alternative explanation for the origins of language. Most of this more recent work focuses on the role of imperfect cultural transmission and abstracts away from the mechanisms of communication. Specifically, models developed to study the cultural evolution of language—both theoretical and computational—often tacitly assume that linguistic signals fully specify the meaning they communicate. They imply that ignoring the fact that this is not the case in actual language use is a justified idealisation which can be made without significant consequences. In this thesis, I show that by making this idealisation, we miss out on the extensive explanatory potential of an empirically attested property of language: its pragmatic plasticity. The meaning that a signal comes to communicate in a specific context usually differs to a certain degree from its conventional meaning. This thesis (i) introduces a model of the cultural evolution of language that acknowledges and incorporates the fact that communication exhibits pragmatic plasticity and (ii) explores the explanatory potential of this fact with regard to language evolution. The thesis falls into two parts. In the first part, I develop the model conceptually. I begin by analysing the components of extant models of general cultural evolution and discuss how models of language change and linguistic evolution map onto them. Innovative use is identified as the motor of cultural evolution. I then conceptualise the cognitive mechanisms underlying innovative language use and argue that they originate in pre-linguistic forms of ostensive-inferential communication. In a next step, the identified mechanisms are employed to provide a unified account of the two main explananda of evolutionary linguistics, the emergence of symbolism and the emergence of grammar. Finally, I discuss the implications of the presented analysis for the so-called proto-language debate. In the second part of the thesis, I propose a computational implementation of the developed conceptual model. This computational implementation allows for the simulation of the cultural emergence and evolution of symbolic communication and provides a laboratory-like environment to study individual aspects of this process. I employ such computer simulations to explore the role that pragmatic plasticity plays in the development of the expressivity, signal economy and ambiguity of emerging and evolving symbolic communication systems. As its main contribution to the study of language evolution, this thesis shows that a model of linguistic cultural evolution that incorporates the notion of pragmatic plasticity has the potential to explain two crucial evolutionary puzzles, namely (i) how language can emerge from no language, and (ii) how language can come to exhibit the appearance of design for communication. The proposed usage-based model of language evolution bridges the evolutionary gap between no language and language by identifying ostensive-inferential communication as the continual aspect present in both stages, and by demonstrating that the cognitive mechanisms involved in ostensive-inferential communication are sufficient for the transition from one stage to the other.
Keywords: Linguistics; language evolution